Enhancing Arabic Vocabulary Mastery through Tafsir al-Shawi: A Pedagogical Approach in Islamic Education - Asep Sunarko (Universitas Islam Internasional Darullughah Wadda'wah, 2025)
This study examines the pedagogical use of Tafsir al-Shawi as an authentic linguistic resource for enhancing Arabic vocabulary mastery in Islamic educational contexts, particularly in pesantren. The study aims to explore how exegetical explanations support learners’ semantic understanding, morphological awareness, and contextual vocabulary retention beyond rote memorization. Using a qualitative descriptive design, data were collected through classroom observations, semi-structured interviews, and document analysis involving Arabic teachers and intermediate-level students at a pesantren in Wonosobo, Indonesia. The findings indicate that Tafsir al-Shawi facilitates vocabulary development through contextual interpretation, semantic elaboration, and root-based morphological analysis. Pedagogical strategies derived from its use include lexical highlighting, semantic mapping, cross-verse comparison, and guided meaning construction, which promote deeper cognitive processing and long-term retention. Although students initially encountered challenges related to classical Arabic style and time constraints, teacher scaffolding effectively mitigated these difficulties. This study concludes that tafsir-based vocabulary instruction offers a viable pedagogical model that bridges classical Islamic scholarship with contemporary Arabic language pedagogy, contributing to both lexical competence and Qur’anic literacy.